Analisis Peran Kompetensi Sumber Daya Manusia dalam Meningkatkan Kinerja Karyawan - Elisabeth Yusri Ratna Nehe; Enik Rahayu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyze the role of human resource competencies in improving employee performance at Klinik Rizky Putri Husada. The study focuses on how employees’ mastery of knowledge, technical and non-technical skills, as well as work attitudes, contributes to the effectiveness, efficiency, and quality of clinic services. To address this issue, the study refers to human resource management and performance management theories, including professional and interpersonal competencies as key performance determinants. Data were collected through in-depth interviews, direct observation, and documentation related to work practices and employee competency development, and then analyzed qualitatively using thematic analysis. The study concludes that human resource competencies play a strategic role in achieving employee performance. Mastery of knowledge and technical skills serves as the primary foundation, while non-technical skills, work attitudes, and continuous competency development act as drivers of service success. Employee performance tends to improve with increasing competency mastery, making holistic and systematic human resource management, including training, mentoring, and periodic evaluation, essential to ensure professional and satisfactory clinic services.